Colimitation assessment of phytoplankton growth using a resource use efficiency approach in the Bay of Seine (French-English Channel). (15th March 2022) - Serre-Fredj, Léon; Chasselin, Léo; Jolly, Orianne; Jacqueline, Franck; Claquin, Pascal
Abstract: Eutrophication and dystrophy are two of the main problems affecting coastal ecosystems. In the Bay of Seine, phosphorus (P) inputs from the Seine estuary have been largely reduced in the last decade, in contrast to nitrogen (N), which leads to high N/P ratio inputs. To study the effect of dystrophy, an enrichment bioassay using water sampled from the Bay of Seine was repeated 19 times over a period of 18 months with six different enrichments. After a few days, chlorophyll a (chl a ), alkaline phosphatase activity (APA), transparent exopolymeric particles (TEPs), cytometric size structure, and maximum quantum yield of photosystem II were measured. The data provide strong evidence for an N & P colimitation system in the vast majority of the incubations, as only the N + P and N + P + Si enrichments supported phytoplankton growth, and Si only appeared to play a secondary role in our incubations. A N/P ratio of 16 equal to the Redfield ratio was identified as the optimum for balanced growth, as chl a was the highest and TEP and APA production was the lowest at this ratio. To fit the requirements of the colimited system, a new resource use efficiency (RUENP ) calculation was developed to account for N and P colimitation instead of only one nutrient, as is usually the case. This calculation allows better representation of RUE in dystrophic conditions, as found in many highly anthropized ecosystems. The relationships between RUENP and the size structure of the phytoplankton community were explored, and a significant positive correlation between RUENP and larger cells (>2 μm) and a negative correlation with smaller cells (<2 μm) were noted, showing a better use of nutrients by larger cells. This study highlights an increase of RUENP with the phytoplankton cell size in a colimited system. Graphical abstract: Image 1 Highlights: A colimitation system of N & P was highlighted by an enrichment experiment in the Bay of Seine. An optimal N/P ratio of 16 for phytoplankton growth was determined, even in dystrophic systems. A new resource use efficiency (RUENP ) calculation was adapted to a colimited system. RUENP positively correlated with larger cells and negatively correlated with smaller cells.